Synthesis of 2-azido-2-deoxy- and 2-acetamido-2-deoxy-D-manno derivatives as versatile building blocks. (February 2020) - Alex, Catherine; Visansirikul, Satsawat; Zhang, Yongzhen; Yasomanee, Jagodige P.; Codee, Jeroen; Demchenko, Alexei V.
Abstract: Reported herein is the synthesis of a number of building blocks of 2-amino-2-deoxy-d -mannose from common d -glucose precursors. Graphical abstract: Image 1 Highlights: Chemical synthesis of a variety of derivatives of mannosamine has been completed using different approaches. The synthesized compounds can be used as glycosyl donors or glycosyl acceptors directly. Other modifications of protecting and/or leaving groups can be easily incorporated. The developed approaches are expected to expedite the synthesis of microbial glycans containing 2-acetamido-d -manno residues.